The nalco guide to boiler failure analysis - Flynn, Daniel J.; Port, Robert D.; Nalco Chemical Company (New York : McGraw-Hill, 2011)
'A comprehensive, up-to-date guide to boiler failure from Nalco, the world's leading water treatment and process improvement companyNalco Guide to Boiler Failure Analysis, Second Edition offers complete coverage of the improved methods to identify and eliminate boiler failure that have emerged since the first edition was published. Investigations into why equipment fails in the steam processes and how to prevent the failures continue to increase. Utilizing the knowledge obtained from failure analysis in the initial engineering of the systems and processes can reduce the potential risks involved with the commissioning of new equipment. Improvements in operating practices can minimize the risk of failure when the mechanisms are understood. This in-depth guide expands the discussion around the known mechanisms of failure and in turn helps in prevention going forward. This will yield to increased asset protection and the longevity of equipment, resulting in a more favorable return on capital.Nalco Guide to Boiler Failure Analysis, Second Edition Contains approximately 200 color illustrations Includes case studies in each chapter Features new coverage of flow accelerated corrosion and fireside failure Covers microstructure and macrostructure failures Includes U.S. customary and SI units throughout Offers an understanding of why equipment fails with engineering solutions, operational changes, and different chemistries to prevent future failures Helps you to avoid equipment or system failure, lost production, and downtime expense, and to improve safety Authoritative coverage: Water and Steam Formed Deposits; Cause of Deposition; Deposit Related Problems; Short-Term Overheating; Long-Term Overheating; Waterside Corrosion; Caustic Corrosion; Low pH During Service; Hydrogen Damage; Phosphate Corrosion; Chelant and Complexing Agent Corrosion; Oxygen Corrosion; Corrosion During Cleaning; Stress Assisted Corrosion; Parting; Graphitic Corrosion; Dealloying; Waterside Flow-Related Damage; Cavitation; Flow Accelerated Corrosion; Erosion; Cracking; Corrosion Fatigue; Stress Corrosion Cracking; Oil Ash Corrosion; Coal Ash Corrosion; Waterwall Fireside Corrosion; Cold End Corrosion; Dew Point Corrosion; Erosion; Forming Defects; Welding Defects'--
'Presented by Nalco, the world's leading water treatment and process improvement company, this is a comprehensive, up-to-date guide to boiler failure--from material defects to corrosion and cracking' --
Machine generated contents note: Section 1 - Deposits on the Water and Steam Side -- Water and Steam Formed Deposits -- Cause of Deposition -- Deposit Related ProblemsSection 2 - Overheating -- Short Term Overheating -- Long Term OverheatingSection 3 - Waterside Corrosion and Damage -- Waterside Corrosion -- Caustic Corrosion -- Low pH During Service -- Hydrogen Damage -- Phosphate Corrosion -- Chelant and Complexing Agent Corrosion -- Oxygen Corrosion -- Corrosion During Cleaning -- Stress Assisted Corrosion -- Parting -- Graphitic Corrosion -- Dealloying -- Waterside Flow Related Damage -- Cavitation -- Flow Accelerated Corrosion -- ErosionSection 4 -Cracking -- Cracking -- Corrosion Fatigue -- Stress Corrosion CrackingSection 5 - Fireside Corrosion and Damage -- Oil Ash Corrosion -- Coal Ash Corrosion -- Waterwall Fireside Corrosion -- Cold End Corrosion -- Dew Point Corrosion -- ErosionSection 6 - Material Defects -- Forming Defects -- Welding DefectsGlossary -- Bibliography -- Book Index.
Prev. ed. by Robert D. Port, Harvey M. Herro.
Includes bibliographical references (p. 577-580) and index.
Keywords: Steam-boilers -- Failures -- Handbooks, manuals, etc; Steam-boilers -- Safety measures -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING / Mechanical